Deposisi Kalsium Karbonat pada Ti-6Al-6Mo[CALCIUM CARBONATE DEPOSITION ON TI-6AL-6MO] - Dwijaya, Made Subekti; Utomo, Muhammad Satrio; Ramadhanty, Syafira Ajeng; Rokhmanto, Fendy; Purawiardi, Ibrahim; Senopati, Galih; Erryani, Aprilia (Jurnal Metalurgi, 2021)
Osseointegration is one of important property in development of implant materials for orthopedic applications. While biocompatible metallic materials such as titanium alloys should already have adequate biocompatibility properties as implant materials, their osseointegration property could be further improved by bioceramic coating. Calcium carbonate (CaCO3) and hydroxyapatite are two major bioceramics in bones that can be utilized to improve the osseointegration property of metallic implant materials. Current challenge on bioceramic coating of metallic implant materials is to obtain coating method that is facile and economically feasible for implementation in the industry. Here we propose a simple and straightforward method to deposit calcium carbonate on Ti-6Al-6Mo. We utilize two common biomimetic solutions, the phosphate buffer saline (Dulbecco’s PBS) and supersaturated calcification solution (SCS) to induce the calcium carbonate formation on the Ti-6Al-6Mo surface. Microstructural and elemental observations by scanning electron microscope (SEM) – energy dispersive x-ray (EDX) has shown the presence of calcium carbonate on the surface of the Ti-6Al-6Mo immersed in SCS. Moreover, the crystallography analysis by x-ray diffraction (XRD) also confirmed the formation of calcium carbonate on the surface of Ti-6Al-6Mo. We also studied the proposed method on pure Ti (>95%) as comparison and similar outcomes were also observed. The effect on duration of immersion was also accounted in current setting. The outcomes of immersion duration for 7 and 10 days were not significantly different.